Role Playing Raises Communication Skills Among Children Aged Four to Five: Bermain Peran Meningkatkan Keterampilan Komunikasi di Kalangan Anak Usia Empat hingga Lima Tahun - Qatrunnada Salsabila Rohadatul 'Aisy; Luluk Iffatur Rocmah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Early childhood is a crucial developmental period where language and interaction abilities support social, emotional, and cognitive growth. Specific Background: Children aged 4–5 years at TKIT Al-Uswah Prigen demonstrated limited verbal participation, difficulty responding to questions, and low engagement in two-way communication due to teacher-centered learning and limited speaking opportunities. Knowledge Gap: Previous studies discussed role-playing in early childhood but rarely focused on macro role-playing integrated with thematic learning and standardized communication indicators for children aged 4–5 years. Aims: This study aimed to increase communication skills of children aged 4–5 years through macro role-playing activities. Results: Classroom Action Research conducted in three cycles showed progressive improvement in communication achievement from 50% in the pre-cycle to 59% in Cycle I, 67% in Cycle II, and 78% in Cycle III, indicating improvement in expressing ideas, listening, and responding using complete sentences. Novelty: The study applies macro role-playing combined with thematic learning and structured observation indicators tailored to early childhood communication development. Implications: The findings provide practical guidance for educators to implement structured role-playing activities to support verbal interaction, vocabulary development, and social communication in early childhood learning environments. Highlights: Structured Dramatization Scenarios Increased Learners’ Ability to Express Ideas and Respond Using Complete Sentences. Repeated Classroom Action Cycles Demonstrated Steady Progress in Listening, Vocabulary Use, and Two-Way Dialogue Participation. Teacher-Guided Thematic Activities Encouraged Confidence and Broader Social Interaction During Learning Sessions. Keywords: Macro Role Playing, Early Childhood Communication, Classroom Action Research, Thematic Learning, Verbal Interaction